If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + -4y = 25 Solving -1x + -4y = 25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4y' to each side of the equation. -1x + -4y + 4y = 25 + 4y Combine like terms: -4y + 4y = 0 -1x + 0 = 25 + 4y -1x = 25 + 4y Divide each side by '-1'. x = -25 + -4y Simplifying x = -25 + -4y
| 8(-16)/5(-8)-3(-13) | | 4x+4+6x-24=110 | | 5.1x-9.4=-.22 | | 4x-10+1-x= | | 4x+4=6x-24 | | 3x^3+21y^2+18= | | 1.88f+32.01= | | 72/x=24 | | 0=6x^2-12x | | 0=x^3-6x^2-9x+14 | | -9-6r+5-5r= | | 1.88+32.01= | | 156-9x=10x+15 | | 78/x=6,5 | | 9(x+2)=3(x+16) | | 1-10x+9x-8= | | 46=2x+3 | | 6(x-4)=56-4x | | 2(x^2-5x)=2x+18 | | 17/5=v/12 | | 24u^6-9u^5/3u^2 | | 3x-3=114-10x | | 2K-2k= | | 7(t+9)+5+t=0 | | 1/3w-8/5=-3/2 | | 5x+4y+2xy=12 | | 6x-16=2x+3 | | 1/3(4/5)=-4/5 | | -8/9-1/2u=-8/3 | | 9a-3(4-x)=20 | | 15/13x=35 | | x(3+12x)=42 |